Annual Plan 1993-94 Volume-I an Overview Government of Assam - Planning Commission (Planning Commission, 1993)
Assam is located in the heartland of the country’s North Eastern Region comprising Assam, Meghalaya, Arunachal Pradesh, Manipur, Mizoram, Nagaland and Tripura and provides the corridor for the other six States of the North Eastern Region. Assam has an area of 78,438 square Kilometres com- pricing of 63,116 square Kilometres of plan areas and 15,322 square Kilometres of hill areas. According to 1991 census, Assam has a population of 2.22 crores comprising of 1.15 crores male and 1 .07 crores female population. the density of population is 284 persons per square Kilometres as compared to all India average of 267.
Government of Assam, Planning and Development Department